KERAGAMAN MAKAN MINIMUM SEBAGAI FAKTOR DOMINAN STUNTING PADA ANAK USIA 6-23 BULAN DI KABUPATEN KUPANG - Irmawati Apriany Thobias; Kusharisupeni Djokosujono (JURNAL KESMAS DAN GIZI (JKG), 2021)
Background: Stunting in children is one of the things that most significantly hinders human development, which globally affects around 162 million children under 5 years (WHO, 2017). Kupang Regency is one of the contributors to the stunting rate with a prevalence of 46.2% in 2013 and increasing in 2019 to 50.3% (SSGBI, 2019). Objectives: This study aims to determine the factors most associated with the incidence of stunting in children 6 -23 months in Kupang Regency. Methods: This study used secondary data from the results of the 2019 YASATU NGO survey with the simple random sampling method, with a sample of 166 children aged 6-23 months. The variables analyzed consisted of the dependent variable stunting, the independent variables: maternal age and education, age and sex of the child, breastfeeding status, minimum dietary diversity, minimum meal frequency, and minimum acceptable diet. Results: The bivariate analysis showed that there hadn’t a relationship between maternal age, maternal education, child age, child sex, breasfeeding status on the incidence of stunting. Meanwhile, there was a significant relationship between minimum dietary diversity (MDD), minimum meal frequency (MMF), minimum acceptable diet (MAD) on the incidence of stunting. The final result of multivariate analysis showed that minimum dietary diversity had the greatest Odds Ratio (OR=12,341; CI 95%=3,118-48,841). It was controlled by breastfeeding status, minimum meal frequency and minimum accpetable diet. Conclusion: Minimum dietary diversity is a dominant factor of stunting in children aged 6-23 months in Kupang Regency. Children who did not meet MDD have 12,3 times higher risk of stunting than those who meet MDD.